2015
DOI: 10.1111/1475-6773.12415
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Reflection in Primary Care Practice Redesign

Abstract: Trust and reflection appear to play a key role in moderating relationships, sensemaking, and learning in practices undergoing practice redesign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…These characteristics include aspects of practice culture and team organization, leadership structure, financial stability, and patient demographic characteristics that have also been shown to be associated with practices using QI strategies. 52,[54][55][56] Our study also showed that practices with ability to extract and use EHR clinical quality data had higher mean CPCQ strategies scores. This finding is especially relevant in light of recent research from EvidenceNOW showing that smaller practices face considerable challenges in extracting and using the EHR data needed for QI.…”
supporting
confidence: 58%
“…These characteristics include aspects of practice culture and team organization, leadership structure, financial stability, and patient demographic characteristics that have also been shown to be associated with practices using QI strategies. 52,[54][55][56] Our study also showed that practices with ability to extract and use EHR clinical quality data had higher mean CPCQ strategies scores. This finding is especially relevant in light of recent research from EvidenceNOW showing that smaller practices face considerable challenges in extracting and using the EHR data needed for QI.…”
supporting
confidence: 58%
“…In the case of the networks and communications construct, we used an additional model from Lanham and colleagues to classify the sub-constructs, since emerging subcodes aligned with characteristics of work relationships that Lanham and colleagues had previously identified [18][19][20]. CFIR defines the networks and communications construct as being about relationships: "the nature and quality of webs of social networks and the nature and quality of formal and informal communications within an organization" [13].…”
Section: Synthesis and Analysismentioning
confidence: 99%
“…When patients trust their family doctors, it is much easier for medical staff to moderate relationships with patients, to make sense to medical interventions and to teach the patients how to live with their conditions (Lanham et al, 2015). If patients trust the attending physicians and nurses in emergency department, level of anxiety decreases and specific fears become less pronounced (Jay, 1996), explaining why mistrust to hospital staff relates to increased fear of hospitalisation.…”
Section: Discussionmentioning
confidence: 99%